Discrepancy Principle and Convergence Rates in Regularization of Monotone Ill-Posed Problems - Nguyen Buong (Український математичний журнал, 2003)
The convergence rates of the regularized solution as well as its Galerkin approximations for nonlinear monotone ill-posed problems in a Banach space are established on the basis of the choice of a regularization parameter by the Morozov discrepancy principle. На основі вибору параметра регуляризації відповідно до принципу нев'язки Морозова встановлено швидкості збіжності як регуляризованих розв'язків нелінійних монотонних некоректних задач у банаховому просторі, так і їх наближень Гальоркіна.